Effect of immunosuppressant anti-bursacyte globulin and anti-thymocyte globulin on hot defense against Salmonella Pullorum infection in chicks - Ara, Anjuman; Tiwary, B K; Ahmed, K A; Rawat, M; Mishra, S C; Saxena, V K; Soman, J P (The Indian Journal of Animal Sciences, 2011)
The study was carried out to understand the relative role of B and T cells in host defense against pullorum disease, in chicks vaccinated with formalin inactivated Salmonella Pullorum vaccine and serologically immunosuppressed with duck anti-thymocyte globulin (DATG) and duck anti-bursacyte globulin (DABG). Both immunosupresssants showed a high citotoxicity titre (512) and were specific in their action. DABG wan effective for B cells as was indicated by the suppression of humoral antibody when detected by ELISA, whereas DATG was immunosuppressant for T cells as detected by lymphocyte against Salmonella Pullorum test(LBT). The study concluded that cellular immune response plays a defnite role in protection against Salmonella Pullorum lnfection in chicks. However, some role 1s also played by humoral immunity in defense mechanism and both are involved in protection.